Effects of cognitive and motor tasks on the walking speed of individuals with chronic stroke - Goh, Lee-Yin. (Medicine (Baltimore), 2017)
Walking speed is a measure of gait performance after a stroke and a predictor of community ambulatory competence. Although gait decrements during a cognitive or motor task after stroke are well-documented, the differential effects of motor and cognitive tasks on the comfortable and maximum walking speeds of individuals with chronic stroke have not been investigated. This study aimed to compare the effects of cognitive and motor tasks on the comfortable and maximum walking speeds of individuals with chronic stroke. This is a cross-sectional study. Thirty community-dwelling chronic stroke individuals were included. Time taken to complete the 10-meter Walk Test under various conditions, including walking alone, walking while completing a cognitive task, and walking while completing a motor task, was recorded, with each condition performed at comfortable as well as maximum walking speeds. Accuracy in performing the cognitive tasks was also assessed. The cognitive and motor tasks caused decrements in both comfortable and maximum walking speeds (P ≤ 0.001). The cognitive task had a greater influence than the motor task on maximum walking speed (P < 0.01). Individuals with chronic stroke tend to prioritize task accuracy and completion over maintaining walking speed. This phenomenon was more evident during the cognitive task than the motor task and was especially evident at maximum walking speed.